Artificial Intelligence and M-Learning in Arabic Countries: Innovations, Trends, and Regional Perspectives - Alasmari, Talal (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study addresses the significant knowledge gap in understanding the regional dynamics of artificial intelligence (AI) in education within the Arabic countries. It applied a bibliometric analysis of research published on the Scopus database from 2003 to 2024 to map publication trends, collaborative structure, and emerging research themes. The findings indicate that there has been a significant increase in research output since 2018, with a notable shift from general eLearning applications to specialized AI applications, specifically in mobile learning (M-learning) environments. These applications enhance adaptive, personalized, and resilient educational practices. Key findings include the anticipation of ChatGPT’s prominence in 2024 as a research focus, strong cross-country collaborations, especially with Saudi Arabia, and a growing interest in AI applications in higher education. Additionally, the study highlights the research advancements in AI ethics, natural language processing (NLP) in education, and AI-powered M-learning platforms. The study applied Bradford’s and Lotka’s laws to uncover patterns in journal distribution and author productivity, indicating a concentration of research among a core set of journals and authors. However, challenges remain, including the need for increased international collaboration and addressing ethical considerations in AI implementation. The in-depth study provides useful information for researchers, teachers, and policymakers, focusing on how AI can change M-Learning and the need for culturally aware and morally sound methods for incorporating AI into Arabic school systems.